Kirkwood–Buff theory of molecular and protein association, aggregation, and cellular crowding - Gee, Moon Bae; Smith, Paul E. (My University, 2009)
An analysis of the effect of a cosolvent on the association of a solute in solution using the Kirkwood–Buff theory of solutions is presented. The approach builds on the previous results of Ben-Naim by extending the range of applicability to include any number of components at finite concentrations in both closed and semiopen systems. The derived expressions, which are exact, provide a foundation for the analysis and rationalization of cosolvent effects on molecular and biomolecular equilibria including protein association, aggregation, and cellular crowding. A slightly different view of cellular crowding is subsequently obtained. In particular, it is observed that the addition of large cosolvents still favors the associated form even when traditional excluded volume effects are absent
Keywords: Association; Biochemistry; Cellular biophysics; Molecular biophysics; Proteins; Kirkwood-Buff theory